Autonomy, Moral Constraints, and Markets in Kidneys. - Kerstein, Samuel J. (Journal of Medicine & Philosophy, 2009)
This article concerns the morality of establishing regulated kidney markets in an effort to reduce the chronic shortage of kidneys for transplant. The article tries to rebut the view, recently defended by James Taylor, that if we hold autonomy to be intrinsically valuable, then we should be in favor of such markets. The article then argues that, under current conditions, the buying and selling of organs in regulated markets would sometimes violate two Kantian principles that are seen as moral constraints. One principle forbids expressing disrespect for the dignity of humanity; the other forbids treating others merely as means. In light of the moral danger posed by regulated markets, the article advocates an alternative way of diminishing the current organ shortage, namely opt-out systems of cadaveric organ donation.